2016
DOI: 10.1007/s12161-016-0544-0
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Honey from Its Bee Origin via Chemical Profiles and Mineral Content

Abstract: Raw honeys from four different bee species, namely the honey bees and stingless bees, were classified based on its chemical profiles, mineral contents and heavy metals. Chemical profiles including proximate composition, predominant sugars, hydroxymethylfurfural content, and diastase activity were determined following official methods while mineral and heavy metals contents were obtained from atomic adsorption spectrometry (AAS) and inductively coupled plasma-mass spectrometry (ICP-MS) measurements, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
66
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 35 publications
11
66
3
1
Order By: Relevance
“…[20] There is limited publication available on Malaysian stingless bee honey. [21][22][23] Most of the publications reported are on the physicochemical and antioxidant properties. However, there is no information on organic acids of Malaysian stingless bee honey.…”
mentioning
confidence: 99%
“…[20] There is limited publication available on Malaysian stingless bee honey. [21][22][23] Most of the publications reported are on the physicochemical and antioxidant properties. However, there is no information on organic acids of Malaysian stingless bee honey.…”
mentioning
confidence: 99%
“…PCR amplification of the Kelulut A1 (Lane 9), Kelulut A2 (Lane 10), Commercial X (Lane 12) and Commercial Z (Lane 14) samples were unsuccessful probably due to degradation of DNA molecules into fragments smaller than 150 bp. These honey samples also have higher hydroxymethylfurfural (HMF) content in the range of 30.0-295.2 mg kg À1 as compared to other honey samples with HMF content less than 24 mg kg À1 (Kek et al, 2017a). The HMF is one of the common intermediate product of Maillard reaction that appears naturally in honey, increasing with heating, improper storage temperature and longterm storage (Furkan Yardibi & Gumus, 2010;Fechner et al, 2016).…”
Section: Capacity Of Dna For Pcr Amplificationmentioning
confidence: 98%
“…In addition, the metabolites contents are varied due to different stingless bee species might secrete different types of enzymes to Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 16 July 2018 doi:10.20944/preprints201807.0291.v1 the foraged nectar. According to Kek et al, [34], the composition of honey is probably affected by the type of bee because honey-making process is highly related to enzymes added by the bees. Therefore, bee species origins could be suggested as reliable classifier in rapid determination of honey quality in terms of originality and purity using NMR-LCMS-based metabolomics approach.…”
Section: Pls-da (Uhplc-qtof Mass Spectrometric Data)mentioning
confidence: 99%
“…Kek et al, [34] showed that the entomological origins of stingless bee honeys (four different bee species) can be used as classifier to classify raw honeys using their chemical profiles and mineral contents. According to Ramón-Sierra et al, [33], it is possible to differentiate honey samples in terms of bee species origins using metabolomics tools.…”
Section: Introductionmentioning
confidence: 99%